2019
DOI: 10.14503/thij-16-5988
|View full text |Cite
|
Sign up to set email alerts
|

Transapical Implantation of Edwards Sapien XT Valve to Close a Left Ventricular Outflow Tract Pseudoaneurysm

Abstract: A 58-year-old man presented with symptomatic high-degree atrioventricular block and congestive heart failure. His medical history included a bicuspid aortic valve (AV), aortic stenosis, and 3 bioprosthetic AV replacement operations-the last, 25 years before, to place a homograft. At the current admission, the patient underwent pacemaker implantation to treat the heart block. Then, a structural AV abnormality was detected. A transesophageal echocardiogram (TEE) showed paravalvular leak and a new finding: a 1.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…The percutaneous closure of LVPA was performed on an urgent basis in 3 (3.2%) patients [13,20,23]. The percutaneous procedures succeeded on the first try in 79 (84.9%) patients, whereas failures were encountered during the percutaneous manoeuvres in 14 (15.1%) patients [10,11,14,24,30,44,51,54,[63][64][65][66][67]70]. Of the latter 14 patients, the percutaneous closure of LVPA eventually succeeded in 12 (85.7%) patients, whereas it had to convert to open surgery in 2 (14.3%) patients [66,67].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The percutaneous closure of LVPA was performed on an urgent basis in 3 (3.2%) patients [13,20,23]. The percutaneous procedures succeeded on the first try in 79 (84.9%) patients, whereas failures were encountered during the percutaneous manoeuvres in 14 (15.1%) patients [10,11,14,24,30,44,51,54,[63][64][65][66][67]70]. Of the latter 14 patients, the percutaneous closure of LVPA eventually succeeded in 12 (85.7%) patients, whereas it had to convert to open surgery in 2 (14.3%) patients [66,67].…”
Section: Resultsmentioning
confidence: 99%
“…The 66 recruited articles included 1 (1.5%) retrospective study [ 22 ], 4 (6.1%) case series [ 36 , 48 , 52 , 65 ], 43 (65.2%) case reports [ 5 , 7 , 9 – 11 , 13 , 14 , 17 21 , 24 , 25 , 27 – 32 , 34 , 35 , 38 – 40 , 42 , 43 , 45 47 , 49 51 , 54 , 55 , 58 , 60 , 62 , 63 , 66 68 , 71 ], 14 (21.2%) medical images [ 12 , 15 , 16 , 23 , 26 , 33 , 41 , 44 , 53 , 56 , 59 , 61 , 69 , 70 ], and 4 (6.1%) proceeding abstracts/posters [ 8 , 37 , 57 , 64 ]. There were a total of 93 patients, including 58 (63.0%) male and 34 (37.0%) female (χ 2 = 12.5, p = 0.001), with a male-to-female ratio of 1.7 : 1 (gender of 1 patient was unknown).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Published papers have described aortic valve replacement alone or combined with individualized reconstruction procedures (i.e., simple aneurysmal suture or reinforced with various materials, homograft aortic root replacement, and coronary artery bypass grafting) as of current open-surgery options [13][14][15]. Few authors have described successful percutaneous device-therapy of P-MAIVF using various devices (coil embolization, septal occluder devices, vascular plugs, transapical implantation of an Edwards Sapien XT valve-in-valve fashion) as an alternative when surgery is not appropriate [32][33][34]. Recently, Boi et al reported the first successfully exclusion of a P-MAIVF by transapical transcatheter implantation of a balloon-expandable Edwards Sapien 3 Ultra valve in a 78-year-old man with concomitant severe aortic stenosis [35].…”
Section: Discussionmentioning
confidence: 99%